Iodine‐Catalyzed Selective Synthesis of 2‐Sulfanylphenols via Oxidative Aromatization of Cyclohexanones and Disulfides. Issue 14 (20th September 2013) - Ge, Wenlei; Zhu, Xun; Wei, Yunyang
Abstract Iodine‐catalyzed intermolecular dehydrogenative aromatizations of six‐membered cyclohexanones for the selective synthesis of 2‐sulfanylphenols have been developed. Both aryl and alkyl disulfides can be used as sulfanylation reagents to give the desired products in good yields under the optimized reaction conditions. The catalytic reaction uses dimethyl sulfoxide or oxygen as the terminal oxidant and avoids the use of transition metal catalysts. In addition, α‐sulfanyl enones could also be obtained via an iodine‐catalyzed oxidative system from simple cyclic ketones using dimethyl sulfoxide as the oxidant. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>